2010
DOI: 10.1007/s11033-010-0559-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of enzymes related to juvenile hormone metabolism in the silkworm, Bombyx mori L.

Abstract: The physiological balance of juvenile hormone (JH) in insects depends on its biosynthesis and degradation pathway. Three key enzymes namely, juvenile hormone esterase (JHE), juvenile hormone epoxide hydrolase (JHEH) and juvenile hormone diol kinase (JHDK) are required for degradation in insects. Our present results showed that JHE and JHEH exhibited expression in almost all the tissues. This indicated that JHE and JHEH might degrade JH simultaneously. In addition, the highest levels of JHDK were observed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Out study showed that the JHEH gene was obviously up-regulated in larvae (L) compared with papue (P), resulting in a relatively lower JH titre in larvae (plot A, Figure 6); the JHAMT gene was not shown to be up-regulated, whereas the JHEH shown to be down-regulated in adults (A) compared with larvae (L), resulting in a higher JH titre in adults (plot B, Figure 6). These results were congruent with those of previous studies in other insect groups (Yang et al, 2011;Wijesekera and Dauwalder, 2016). Comparison of the juvenile hormone (JH) signalling pathway genes between different developmental stages: A: larvae (L) and pupae (P); B: larvae (L) and adults (A).…”
Section: Degs In Juvenile Hormone Pathwaysupporting
confidence: 91%
“…Out study showed that the JHEH gene was obviously up-regulated in larvae (L) compared with papue (P), resulting in a relatively lower JH titre in larvae (plot A, Figure 6); the JHAMT gene was not shown to be up-regulated, whereas the JHEH shown to be down-regulated in adults (A) compared with larvae (L), resulting in a higher JH titre in adults (plot B, Figure 6). These results were congruent with those of previous studies in other insect groups (Yang et al, 2011;Wijesekera and Dauwalder, 2016). Comparison of the juvenile hormone (JH) signalling pathway genes between different developmental stages: A: larvae (L) and pupae (P); B: larvae (L) and adults (A).…”
Section: Degs In Juvenile Hormone Pathwaysupporting
confidence: 91%
“…In B. mori, the transcript of JHE was coincident with the JH titer pattern in vivo (Hua-jun et al, 2011). Thus, higher level of JH in L. decemlineata larval hemolymph after 1-3 days' ingestion of dsLdAS-C may upregulate the JHE, JHEH and/or JHDK, which subsequently degrade JH rapidly in L. decemlineata, and lower the JH titer in hemolymph.…”
Section: Ckmentioning
confidence: 86%
“…Larval weight (mg) 4 days after feeding 88.4 ± 4.3 a 86.3 ± 3.8 a 72.2 ± 4.1 b 69.5 ± 3.4 b Rate of the third instar 2 days after feeding 1.00 ± 0.00 a 1.00 ± 0.00 a 0.89 ± 0.04 a 0.93 ± 0.10 a Rate of the fourth instar 4 days after feeding 0.94 ± 0.12 a 0.87 ± 0.23 a 0.28 ± 0.14 b 0.46 ± 0.08 b Larval duration (days) 14.6 ± 0.3 a 15.0 ± 0.3 a 16.1 ± 0.4 b 15.8 ± 0.4 ab Survivorship 6 days after feeding 1.00 ± 0.00 a 0.95 ± 0.00 a 0.98 ± 0.03 a 1.00 ± 0.00 a Pupation rate 1.00 ± 0.00 a 0.95 ± 0.00 a 0.94 ± 0.04 a 0.90 ± 0.06 a Emergence rate 0.95 ± 0.00 a 0.90 ± 0.00 a 0.85 ± 0.05 a 0.90 ± 0.07 a Different lowercase letters in each line indicate significant difference at P value b 0.05. named JH esterase (JHE), JH epoxide hydrolase (JHEH) and JH diol kinase (JHDK) (Hua-jun et al, 2011). In B. mori, the transcript of JHE was coincident with the JH titer pattern in vivo (Hua-jun et al, 2011).…”
Section: Ckmentioning
confidence: 99%
“…4 ). High transcription levels of jheh have been detected in the Malpighian tubules, fat bodies, midgut and epidermis of L. decemlineata ( Lü et al 2015 ) and B. mori ( Yang et al 2011 ). This indicates that JHEH might degrade JH in various tissues ( Lü et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%